Bright blue halloysite/CoAl2O4 hybrid pigments: Preparation, characterization and application in water-based painting. (April 2017) - Zhang, Anjie; Mu, Bin; Luo, Zhihe; Wang, Aiqin
Abstract: Bright blue CoAl2 O4 /halloysite hybrid pigments were prepared via combining chemical co-precipitation and calcination process. The obtained hybrid pigments were characterized by X-ray diffraction, scanning electron microscopy, Fourier transform infrared spectroscopy, high resolution transmission electron microscopy, and ultraviolet–visible spectroscopy. The introduction of halloysite not only decreased the calcining temperature for formation of spinel-type CoAl2 O4, but also enhanced the color properties of CoAl2 O4 pigments including hue, brightness and chroma. The hybrid pigments incoropated 60% halloysite presented excellent color properties ( L *  = 54.6, a *  = −2.5, b *  = −50.4, h *  = 262.21, and C *  = 47.35) and excellent environmental resistance tolerance toward acid, alkali and ultraviolet light. In particular, the hybrid pigments could be well dispersed into water-based paint with good suspension stability. It indicated that the hybrid pigments could be served as a promising pigment with bright blue to be applied in various fields such as ceramics, water based paints, inks, etc. Graphical abstract: Highlights: Bright blue and low-cost halloysite/CoAl2 O4 hybrid pigments were successfully prepared. Introducing of halloysite decreased the calcining temperature to form spinel-type CoAl2 O4 . Incorporating of halloysite was favor of enhancing the color performance of pigments. Hybrid pigments exhibited good suspension stability in water-based painting. Hybrid pigments could be sprayed onto various substrates.